2020
DOI: 10.3389/fnins.2020.00018
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Cholesterol in Modulating the Binding of α-Synuclein to Synaptic-Like Vesicles

Abstract: α-Synuclein (αS) is a presynaptic protein whose aggregation is associated with Parkinson's disease (PD). Although the physiological function of αS is still unclear, several lines of evidence indicate that this protein may play a role in the trafficking of synaptic vesicles (SVs) during neurotransmitter release, a task associated with its ability to bind SVs and promote their clustering. It is therefore crucial to identify the cellular factors that modulate this process. To address this question, using nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 82 publications
2
39
1
Order By: Relevance
“…IPM and OPM lipid mixtures were prepared in the form of small unilamellar vesicles (SUVs) with size distributions centred around 50 nm, as measured using dynamic light scattering (DLS) (see Methods). The utilisation of this form of lipid assemblies enables a direct comparison of the present results with interaction studies previously performed with synaptic-like SUVs (SL-SUVs) composed of dioleoyl-phosphoethanolamine (DOPE), dioleoylphosphatidylcholine (DOPC) and dioleoyl-phosphatidylserine (DOPS) 33 and cholesterol 43 .…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…IPM and OPM lipid mixtures were prepared in the form of small unilamellar vesicles (SUVs) with size distributions centred around 50 nm, as measured using dynamic light scattering (DLS) (see Methods). The utilisation of this form of lipid assemblies enables a direct comparison of the present results with interaction studies previously performed with synaptic-like SUVs (SL-SUVs) composed of dioleoyl-phosphoethanolamine (DOPE), dioleoylphosphatidylcholine (DOPC) and dioleoyl-phosphatidylserine (DOPS) 33 and cholesterol 43 .…”
Section: Resultsmentioning
confidence: 80%
“…c Representative 1 H- 15 N-HSQC CEST spectra of αS in the presence of IPM measured using a 350 Hz continuous wavelength at offsets of 100 kHz (red) and 1.5 kHz (blue). d Comparison of the interaction of αS with SL-SUVs 43 (yellow) and IPM (red) probed with NMR CEST profiles measured using a saturation bandwidth of 350 Hz and offsets of ±1.5 kHz. Data for the SL-SUVs binding 43 were measured at protein and lipid concentrations of 300 μM and 0.06% (0.6 mg/ml), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may suggest that brain-derived human α-synuclein promotes compound fusion in vivo . In support of this idea, several recent studies have reported that α-synuclein induces multivesicular assemblies, leading to tubulation and vesicle-vesicle fusion in vitro , although only at higher concentrations ( Varkey et al, 2010 ; Fusco et al, 2016 ; Man et al, 2020 ). Adding to the complex nature of this phenotype, the fusosomes have characteristics of both fusion and fission events ( Shin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 84%
“…Our results show that the majority of cisternae induced by brain-derived human α-synuclein are disconnected from the plasma membrane, suggesting that they may be recycling endosomes, or alternatively bulk endosomes ( Figure 8 ; Chanaday et al, 2019 ). However, considering that less than 2% of the cisternae had clathrin-coated buds, it is also plausible that brain-derived human α-synuclein induces the formation of cisternae through aberrant vesicle-vesicle fusion, which has been reported for high concentrations of α-synuclein in vitro ( Varkey et al, 2010 ; Fusco et al, 2016 ; Man et al, 2020 ). We think this is unlikely, however, because native α-synuclein does not affect v-/t-SNARE-mediated vesicle fusion at lower concentrations closer to those injected in our experiments ( Diao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 95%